Integration of vertical and lateral erosion in modelling landslide mass flows, debris flows and flash floods - Ruochen Jiang; Wenjun Lu; Shihao Xiao; Xin He; Ruiqiang Bai; Yingyue Han; Mingdong Wei; Dalei Peng; Jian He; Limin Zhang (Journal of Hydrology, 2026)

A Novel LEC Framework Incorporating Source Resolution: Spatiotemporal Evolution and Multi-Scenario Prediction of Soil Heavy Metal Risks - Xiufang Zhao; Kang Hou; Yujie Zhu; Xiaoping Li; Zeyu Liu; Xinyuan Zhu; Ruochen Mei; Luohong Zhang; Xuxiang Li (Journal of Environmental Chemical Engineering, 2026)

Accelerating high-fidelity debris-flow modeling with a super-resolution deep-learning framework - Yunhong Lv; Jian He; Luyu Ju; Ruochen Jiang; Yuran Li; Zening Zhao; Yuanen Pang; Limin Zhang (Engineering Geology, 2026)

Reactant-adsorption induced flexible hydrogen-bond networks on Co–O–Fe electronic bridges for enhanced electro-oxidation of methanol to formate - Haiqing Gong; Ruixiang Ge; Congcong Jian; Ruochen Zhang; Shuo Lu; Min Ma; Jian Tian (Chemical Engineering Journal, 2026)

Frost heave modeling and field verification for arc-bottom trapezoidal lined canals in cold regions - Jianrui Ge; Yaxin Zhang; Ruiqiang Bai; Zhengzhong Wang; Haoyuan Jiang; Ruochen Jiang (Cold Regions Science and Technology, 2026)

A multi-model fusion framework for assessing microscale carbon stock dynamics and ecological quality regulation - Ruoxi Li; Kang Hou; Yuxiang Xue; Bo Zhang; Ruochen Mei; Zhao Liu; Xuxiang Li (Environment, Development and Sustainability, 2026)

Erosion-deposition governs sediment dynamics and amplifies cascading hazards of glacial lake outburst floods - Ruochen Jiang; Wenjun Lu; Shihao Xiao; Xin He; Luyu Ju; Ruiqiang Bai; Mingdong Wei; Limin Zhang (Geomorphology, 2026)

Freeze–thaw cycles control successive glacier landslide hazards in Amney Machen Mountain - Jiaming Ye; Ruochen Jiang; Shihao Xiao; Yingyue Han; Luyu Ju; Wenjun Lu; Ruiqiang Bai; Tao Yao; Limin Zhang (Landslides, 2026)
Climate change has markedly increased the susceptibility of glacier-related landslides to alpine environments, leading to cascading processes with catastrophic impacts. Nevertheless, their triggering processes remain inadequately understood, which hinder robust hazard assessments and effective risk mitigation. Glacier collapses and cascading processes have been frequently observed at Xiaoma Gully in Amney Machen Mountain. Based on remote sensing, meteorological data analyses, field surveys and numerical simulations, glacier landslide hazard chains in this gully are reconstructed and associated triggers are identified. Results indicate that extreme diurnal freeze–thaw cycles drove the Xiaoma glacier collapses, and extreme temperature and precipitation accelerated glacier instabilities. The 365-day cumulative number of diurnal freeze–thaw cycles is identified as a critical precursor for initiating glacier collapses, serving as a quantitative indicator to characterize the long-term impact of freeze–thaw cycles. The application of this indicator to the Kolka Glacier collapse at Genaldon Valley in Russian Caucasus further demonstrates its feasibility. Furthermore, the catastrophic glacier landslide cascades underwent hazard-type transformation and displayed high mobility, reaching peak flow velocities over 30 m/s. This study sheds light on early warning and emergency management of glacier collapses in alpine regions.

Quantifying the adaptability of China’s dominant maize varieties to future climate change: A combined approach of crop modeling and explainable machine learning - Mengna Li; Ruochen Li; Zhiwei Zhang; Yusong Xu; Fu Chen; Yongdeng Lei (Computers and Electronics in Agriculture, 2026)

Comparison and Optimization of Intermittent Aeration/Interval Aeration for Enhancing Nitrogen Removal in Continuous Flow Anaerobic/Oxic/Anoxic Processes - Ruochen Hu; Zeming An; Yuanqi Gu; Xinjie Gao; Liang Zhang; Yongzhen Peng (Bioresource Technology, 2026)

Sustainable vertical barriers using solidified marine mud: Hydraulic and mechanical behavior of lithium slag-fly ash geopolymer composites - Zhongxing Ping; Haoqing Xu; Songyu Liu; Yong Yue; Ruochen Wang; Nan Zhang (Process Safety and Environmental Protection, 2026)

Research on Eliminating Knowledge Contradictions in the Field of Water Pollution Control Based on Extenics-Conjugate Analysis - Jianxun Li; Yujie Wu; Yanying Shang; Ruochen Zhang; Heng Lu (Water, Air, & Soil Pollution, 2026)

Ginkgetin inhibits non-small cell lung cancer via the HSP90-AKT signaling pathway - Ruochen Li; Haotian Gao; Mingxiao Wang; Yong Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Overcoming acidic constraints: A bio-inspired cu-bilirubin nanozyme with superior neutral-pH peroxidase and laccase-like activities for selective sensing and removal of formaldehyde and pyrogallic acid - Ruochen Duan; Xiaohui Hao; Ao Shen; Panqing Zhang; Zeyu Zhang; Xuebing Wang; Long Chen; Qingyang Fan; Jiahao Wang; Yunxu Yang (Chemical Engineering Journal, 2026)

Dominant role of CaCl2 in integrated CO2 capture and utilization (ICCU-RWGS) in chloride-based molten salts - Xiaotong Zhao; Fangshu He; Ruochen Yang; Yulan Han; Xiong Zhang; Yang Yang; Haiping Yang; Chunfei Wu (Chemical Engineering Journal, 2026)

Urinary total arsenic, arsenic species, and arsenic methylation capacity: an integrative profiling analysis of microRNAs in plasma and leukocytes - Yaxin Wang; Wending Li; Weiya Li; Yufei Wang; Xuedan Xu; Ruochen Yuan; Xiao Zhang; Jingli Qu; Pinpin Long; Hao Wang; Meian He; Xiaomin Zhang; et al. (Environmental Pollution, 2026)

Simultaneous dual-mode detection and removal of acrolein in food samples via a fluorescent PAA-CDs/Sulfhydryl cotton/SA hydrogel composite - Panqing Zhang; Ruochen Duan; Zeyu Zhang; Lingwei Xue; Xuebing Wang; Long Chen; Qingyang Fan; Jiahao Wang; Yunxu Yang (Food Chemistry, 2026)

Study on the Effect of Elevators in the Vertical Plane on the Motion Performance of a Twin Hybrid Autonomous Underwater Vehicle by Simulation - Jiafeng Huang; Kele Zhou; Hyeung-Sik Choi; Ruochen Zhang; Phan Huy Nam Anh; Dong-Wook Jung; Mai The Vu (Journal of Marine Science and Engineering, 2025)
The Twin Hybrid Autonomous Underwater Vehicle (THAUV) is an underwater monitoring system consisting of a twin buoyant body and a fixed wing mounted between them. It is equipped with two propeller thrusters and a pair of elevators at the aft end. As a new type of underwater vehicle, it combines the long endurance of an underwater glider (UG), the high-speed maneuverability of an autonomous underwater vehicle (AUV), and the ability to carry larger payloads. In this paper, the motion equations of the THAUV are established, and its simulation model is developed using SIMULINK. Computational fluid dynamics (CFD) is further employed to identify hydrodynamic parameters under different elevator size conditions. A case study is conducted to analyze the effects of three different widths of elevators on glide performance, including gliding speed, pitching angle, and gliding trajectory. CFD results show that when the elevator deflection angle is zero, the hydrodynamic forces acting on the THAUV increase as the elevator width increases under identical angle of attack and velocity conditions. Under CFD conditions with fixed angle of attack and flow velocity, the sensitivity of the hydrodynamic characteristics to elevator deflection became significantly more pronounced. Increasing the elevator deflection angle led to substantial growth in the generated hydrodynamic forces. Motion simulations further show that increasing the elevator deflection angle enhances the THAUV’s gliding performance. Comparative results also reveal that glide performance improves with larger elevator width.

Nitrogen-vacancy-rich Co3O4/carbon nitride activating peroxymonosulfate for efficient micropollutant degradation: Dominant role of superoxide radicals - Jiani Qin; Minna Duan; Yi Zhang; Ruochen Hua; Yongqi Zhang; Chuanyi Wang; Bao Pan (Environmental Research, 2025)

Deep eutectic solvent-assisted 3D printing of lignocellulosic biomass - Tingting Wu; Sigit Sugiarto; Udyani Aloka Weerasinghe; Ruochen Yang; Linran Jia; Pek Yin Michelle Yew; Danwei Zhang; Thenapakiam Sathasivam; Pei Lin Chee; Xunchang Fei; Dan Kai (Chemical Engineering Journal, 2025)

High-Resolution Prediction of Thin-Layer Reservoirs Based on Seismic Sedimentology: A Case Study of the Penglaizhen Formation, Western Sichuan Basin, China - Gang Lu; Changcheng Wang; Xiaobing Zhang; Xihe Lu; Ruochen Tang; Sheng Zhang; Zheng Wang (Natural Resources Research, 2025)

Development of a data-driven spatial framework for optimizing vertical greening in high-density Tokyo - Ruochen Ma; Yunchen Xu; Yan Tang; Sihan Zhang; Yuhui Liao; Katsunori Furuya (Sustainable Cities and Society, 2025)

Community-level polycyclic aromatic hydrocarbon exposure and circulating microRNAs: Exploring their origins and regulatory functions in immune cells - Yufei Wang; Wending Li; Xuedan Xu; Yaxin Wang; Qin Jiang; Yutong You; Ruochen Yuan; Xiao Zhang; Yang Xiao; Chan Kong; Tingting Mo; Huan Guo; et al. (Journal of Hazardous Materials, 2025)

Advancements in gas-liquid separation based on membrane contactors: Critical factors enhancing separation efficiency - Helin Wang; Tao Zhang; Ruochen An; Lin Sun; Xiaohui Weng; Zhiyong Chang (Process Safety and Environmental Protection, 2025)

A thermal-hydro-mechanical coupled analysis model for climate-driven movements of valley glaciers (THM-GA 1.0) - Ruochen Jiang; Limin Zhang; Wenjun Lu; Dalei Peng; Xin He; Shihao Xiao; Yingyue Han; Mingdong Wei (Engineering Geology, 2025)

Advancements and Future Perspectives in Biological Nitrogen and Phosphorus Removal Coupled Resource Recovery Processes - Deyi Jiang; Haoyun Wang; Xuandi Cao; Ruochen Wang; Zheqin Dai; Wuxiang Zhang; Haq Nawaz Abbasi; Bing Li; Xingang Wang; Hongliang Dai (Water, Air, & Soil Pollution, 2025)

Role of Dorsolateral Prefrontal Cortex During Motor Preparation on Anticipatory Postural Adjustments - Jiajia Yang; Guifang Zhang; Xiaoyu Gao; Xue Cheng; Zengming Hao; Jinjin Ma; Nanhe Lin; Ruochen Fu; Wai Leung; Ambrose Lo; Yan Li; Hao Xie; et al. (Brain Topography, 2025)

Cessation of manure application diminishes the dissemination potential of antibiotic resistance genes by altering bacterial interaction patterns in soil–lettuce systems - Ruochen Li; Xin Pei; Ming Zhang; Xuhui Deng; Chengyuan Tao; Jiabao Wang; Xueli Chen; Nicholas Clarke; Lidia Sas-Paszt; Zongzhuan Shen; Rong Li; Qirong Shen (Applied Soil Ecology, 2025)

Optimal sowing density and fertilizer rate can increase oat yield by improving root structure, water use efficiency and fertilizer productivity in semi-arid region - Ruochen Zhang; Yue Wang; Malik Kamran; Jianjun Wang; Tao Li; Guiqin Zhao; Chunjie Li (Plant and Soil, 2025)

Constrained multi-objective evolutionary algorithm based on the correlation between objectives and constraints - Jianxia Li; Ruochen Liu; Xilong Zhang; Ruinan Wang (Swarm and Evolutionary Computation, 2025)

The mechanism of human-machine collaboration driving sustainable business models: A single case study from the electric vehicle industry - Yanying Shang; Junfeng Jiang; Ruochen Zhang; Yamin Zhang; Peiqing Liu; Liqi Yu (Journal of Cleaner Production, 2025)

A dual deep learning approach for winter temperature prediction in solar greenhouses in Northern China - Jingxin Yu; Jinpeng Zhao; Congcong Sun; Ruochen Zhang; Wengang Zheng; Linlin Xu; Xiaoming Wei (Computers and Electronics in Agriculture, 2025)

Screening, identification, and application of anaerobic ammonia oxidizing bacteria in activated sludge systems: A comprehensive review - Haoyun Wang; Hongliang Dai; Deyi Jiang; Xuandi Cao; Ruochen Wang; Zheqin Dai; Wuxiang Zhang; Haq Nawaz Abbasi; Bing Li; Guangcan Zhu; Xingang Wang (Journal of Environmental Management, 2025)

Bottom-up nucleation induced conformal crystallization for inverted MA-free perovskite solar cells on textured substrates - Ruochen Liu; Jiawei Xu; Tianxiang Hu; Xiang Li; Kongxiang Wang; Qi Huang; Zhongtao Duan; Hong Liu; Weifan Qian; Haiting Zhou; Chunxiao Cong; Xiaofei Yue; et al. (Chemical Engineering Journal, 2025)

Versatile inulin/trans-ferulic acid/silk sericin nanoparticles-nourished probiotic complex with prolonged intestinal retention for synergistic therapy of inflammatory bowel disease - Yujie Zhang; Xiaojiang Zhang; Lianxi Lv; Sheng Gao; Xiang Li; Ruochen Wang; Pengqian Wang; Feiyu Shi; Junjun She; Ya Wang (Carbohydrate Polymers, 2025)

Estimation and inference of multi-effect generalized geographically and temporally weighted regression models - Zhi Zhang; Ruochen Mei; Changlin Mei (Spatial Statistics, 2024)

Removal of 48 per- and polyfluoroalkyl substances (PFAS) throughout processes in domestic and general industrial wastewater treatment plants: Implications for emerging alternatives risk control - Yueqing Zhang; Ruochen Dong; Feng Ge; Minghui Hong; Zhanghao Chen; Yunqiao Zhou; Jing Wei; Cheng Gu; Deyang Kong (Journal of Hazardous Materials, 2024)

Dairy farm waste: A potential reservoir of diverse antibiotic resistance and virulence genes in aminoglycoside- and beta-lactam-resistant Escherichia coli in Gansu Province, China - Muhammad Shoaib; Minjia Tang; Amjad Islam Aqib; Xuejing Zhang; Zhongyong Wu; Yang Wen; Xiao Hou; Jinpeng Xu; Ruochen Hao; Shengyi Wang; Wanxia Pu (Environmental Research, 2024)

Hypermobility of a Catastrophic Earthquake-Induced Loess Landslide - Shihao Xiao; Limin Zhang; Jian He; Ming Peng; Ruochen Jiang; Wenjun Lu (Engineering Geology, 2024)

Highly efficient photothermal gel cotton fabricated with MXene and liquid metal particles for solar-driven seawater evaporation and permeable energy generation - Jiayan Zhang; Kang Yang; Bowen Zhang; Jie Wang; Xinping Yu; Xinyuan Lu; Xin Lei; Ruochen Fang (Desalination, 2024)

The peculiar role of iodides and formation of iodinated oligomer byproducts upon phenol mineralization with boron-doped diamond anode - Ruochen Liu; Mingjun Ouyang; Shujuan Chen; Saier Wang; Chenwei Liu; Chunyong Zhang; Hua Wu (Chemical Engineering Journal, 2024)

Novel three-stage microalgal cultivation system for lipid production utilizing nutrients derived from refinery waste - Ruochen Wang; Wei Zhu; JiPeng Sun; Chi Zhang; Hongliang Dai; Tiantian Qu (Bioresource Technology, 2024)

Microbial mechanisms for CO2 and CH4 emissions in Robinia pseudoacacia forests along a North–South transect in the Loess Plateau - Wancai Wang; Xiaojun Wang; Ruochen Zhi; Lu Zhang; Shilong Lei; Asma Farooq; Wende Yan; Zilin Song; Chao Zhang (Journal of Environmental Management, 2024)

Initiation mechanism of landslides in cold regions: Role of freeze-thaw cycles - Tianzheng Li; Limin Zhang; Wenping Gong; Huiming Tang; Ruochen Jiang (International Journal of Rock Mechanics and Mining Sciences, 2024)

Pseudomonas syringae pv. coronafaciens, causing a new bacterial halo blight disease on oat (Avena sativa L.) in China - Jianjun Wang; Ruochen Zhang; Hongshan Deng; Xueqin Han; Xuekai Wei; Malik Kamran; James F. White; Guiqin Zhao; Chunjie Li (European Journal of Plant Pathology, 2024)

Molecular characterization of petroleum acids from diverse geological origins via n-Butylsilane reduction - Haojie Hu; Shuofan Li; Yuanfeng Wang; Ruochen Yang; Jianxun Wu; Weilai Zhang; Chen He; Han Li; Yahe Zhang; Di Zhu; Quan Shi (Fuel, 2024)

Self-assembled multifunctional Prussian blue analogues nanocomposite for MRI-guided multimodal therapy for breast cancer - Min Zhang; Yanping Wu; Xingchen Lu; Yuhan Qin; Cong Zhang; Wenjie Gu; Ruochen Gao; Yuanyuan Qi; Meng Wang; Qingli Huang (Chemical Engineering Journal, 2024)

A knowledge-guided Estimation of Distribution Algorithm for energy-efficient Joint Robotic Assembly Line Balancing and Feeding Problem - Chu-ge Wu; Ruochen Zhang; Yuanqing Xia (Swarm and Evolutionary Computation, 2024)

Two-phase strategy for rapid and unbiased assessment of earthquake-induced landslides - Shihao Xiao; Te Xiao; Ruochen Jiang; Haojie Wang; Luyu Ju; Limin Zhang (Engineering Geology, 2024)

Overlooked in-situ sulfur disproportionation fuels dissimilatory nitrate reduction to ammonium in sulfur-based system: Novel insight of nitrogen recovery - Bo Shao; Li Niu; Yuan-Guo Xie; Ruochen Zhang; Wei Wang; Xijun Xu; Jianxing Sun; Defeng Xing; Duu-Jong Lee; Nanqi Ren; Zheng-Shuang Hua; Chuan Chen (Water Research, 2024)

AtHD2D is involved in regulating lateral root development and participates in abiotic stress response in Arabidopsis - Yueyang Chu; Ruochen Duan; Haoran Song; Wenshuo Zhang; Yuxuan Zhou; Yutong Ma; Xiaotong Yin; Lining Tian; Israel Ausin; Zhaofen Han (Journal of Plant Physiology, 2024)

A conceptual model for evaluating the stability of high-altitude ice-rich slopes through coupled thermo-hydro-mechanical simulation - Mingdong Wei; Limin Zhang; Ruochen Jiang (Engineering Geology, 2024)

Fabrication of a porous Urea@MIL-100(Fe)/CI-MCC/SA hydrogel for All-In-One adsorption, removal and fluorescence monitoring of nitrite - Xiaohui Hao; Ao Shen; Ruochen Duan; Panqing Zhang; Lingwei Xue; Xiuqing Zhao; Xuebing Wang; Xue Li; Yunxu Yang (Journal of Hazardous Materials, 2024)

Emerging and legacy per- and polyfluoroalkyl substances (PFAS) in fluorochemical wastewater along full-scale treatment processes: Source, fate, and ecological risk - Yueqing Zhang; Yunqiao Zhou; Ruochen Dong; Ninghui Song; Minghui Hong; Juying Li; Jia Yu; Deyang Kong (Journal of Hazardous Materials, 2024)

Global mapping of forest clumping index based on GEDI canopy height and complementary data - Xingmin Zhao; Jing M. Chen; Yongguang Zhang; Ziti Jiao; Liangyun Liu; Feng Qiu; Jinlong Zang; Ruochen Cao (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Structural analysis of petroleum acids in highly acidic crude oil and deacidification using organic amines - Ruochen Ma; Lingli Jia; Hongyu Zhang; Fahai Cao; Jianhui Shao; Junjie Zhang; Shuiliang Yan; Jun Xu (Fuel, 2024)

An open online simulation strategy for hydrological ensemble forecasting - Yuanqing He; Min Chen; Yongning Wen; Qingyun Duan; Songshan Yue; Jiapeng Zhang; Wentao Li; Ruochen Sun; Zizhuo Zhang; Ruoyu Tao; Wei Tang; Guonian Lü (Environmental Modelling & Software, 2024)

Effect of high-fat diet on cerebral pathological changes of cerebral small vessel disease in SHR/SP rats - Yuchi Zhang; Abdullah Md. Sheikh; Shatera Tabassum; Kenichi Iwasa; Abu Zaffar Shibly; Xiaojing Zhou; Ruochen Wang; Jubo Bhuiya; Fatema Binte Abdullah; Shozo Yano; Yoshihito Aoki; Atsushi Nagai (GeroScience, 2024)

Quantitative evaluation of velocity pulse-like ground motions using spatial rotation technique - Quanbo Luo; Feng Dai; Ruochen Jiang; Weijin Xu; Gang Zhang (Journal of Seismology, 2024)

Investigation into the electrochemical advanced oxidation of p-arsanilic acid: Peculiar role of electrolytes and unexpected formation of coupling byproducts - Lihua Yan; Ruochen Liu; Chunyong Zhang; Degang Fu (Science of The Total Environment, 2024)

One-step processing of waste dredged slurry into planting soil by targeted pretreatment and vacuum filtration - Silin Wu; Xiao Peng; Xiaohui Sun; Zijun Dong; Aizhao Zhou; Lei Zhang; Ruochen Wang (Journal of Environmental Management, 2024)

Environmental economic profiles of expressway construction via life cycle assessment - Yimiao Huang; Xiaokuan Zhao; Ruochen Zhang; Panpan Xie; Guixiang Xue; Guowei Ma (Environmental Impact Assessment Review, 2024)

Drug Release from Surfactant-Containing Amorphous Solid Dispersions: Mechanism and Role of Surfactant in Release Enhancement - Ruochen Yang; Geoff G. Z. Zhang; Dmitry Y. Zemlyanov; Hitesh S. Purohit; Lynne S. Taylor (Pharmaceutical Research, 2023)

Newcastle disease virus forms inclusion bodies with features of liquid-liquid phase separation - Chongyang Wang; Liuyuan Duan; Ting Wang; Wenbin Wang; Yu Han; Ruochen Hu; Qili Hou; Haijin Liu; Juan Wang; Xinglong Wang; Sa Xiao; Ruyi Dang; et al. (Veterinary Microbiology, 2023)

Fertilizing-induced alterations of microbial functional profiles in soil nitrogen cycling closely associate with crop yield - Ruochen Li; Chengyao Ren; Likun Wu; Xinxin Zhang; Xinyi Mao; Zhen Fan; Weili Cui; Wu Zhang; Gehong Wei; Duntao Shu (Environmental Research, 2023)

Genetic and pathogenic characterization of an NADC-34-like isolate of porcine reproductive and respiratory syndrome virus - Yongxin Zhao; Ruiqing Wang; Wei Li; Chenfei Yu; Riteng Zhang; Ruochen Hu; Ruhai Guo; Zengqi Yang; Yefei Zhou; Xinglong Wang (Archives of Virology, 2023)

Simple method for visual detection of nitrite using fluorescence and colorimetry by poly (tannic acid) nanoparticles - Xiaohui Hao; Ao Shen; Mengwen Li; Ruochen Duan; Lala Hou; Xiuqing Zhao; Ziqi Li; Yongwei Zhao; Panqing Zhang; Xuebing Wang; Xue Li; Yunxu Yang (Analytica Chimica Acta, 2023)

Altered microbial P cycling genes drive P availability in soil after afforestation - Ruochen Zhi; Jian Deng; Yuling Xu; Miaoping Xu; Shuohong Zhang; Xinhui Han; Gaihe Yang; Chengjie Ren (Journal of Environmental Management, 2023)

Analytical method for quantifying performance of wicking geosynthetic stabilized roadway - Wuyu Zhang; Xiongyu Tang; Xiaohui Sun; Ruochen Yang; Guoqing Tong; Jun Guo (Geotextiles and Geomembranes, 2023)

Study on Position and Shape Effect of the Wings on Motion of Underwater Gliders - Jiafeng Huang; Hyeung-Sik Choi; Mai The Vu; Dong-Wook Jung; Ki-Beom Choo; Hyun-Joon Cho; Phan Huy Nam Anh; Ruochen Zhang; Jung-Hyeun Park; Joon-Young Kim; Huy Ngoc Tran (Journal of Marine Science and Engineering, 2022)
A typical structure of an underwater glider (UG) includes a pair of fixed wings, and the hydrodynamic force driving the glider forward as descending or ascending in the water is generated primarily by the fixed wings. In this paper, a simplified glider motion model was established to analyze the dynamics in an easier way, and whose simulation results do not differ from the original one. Also, in the paper, the effects of the wing position and wing shape on the UG to the motion were studied. Since no direct analytic approach cannot be performed, the case study of the effects of six different wing positions and three wing shapes on gliding performances which are gliding speed, gliding angle and gliding path were performed through computer simulation. The simulation results revealed that when the fixed wing is located far from the buoyancy center to the tail end, more traveling range is achieved with less energy. Also, effect of the shape difference of the wings were analyzed. Shape changes did not show much difference on the travelling performance of the UG. In addition to these, the transient mode of the UG was studied. To control this, the PID controller for the position of the mass shifter and piston were applied. By application of the PID controller to the linearized dynamics equations, it was shown that the transient behavior of the UG was quickly and steadily controlled.

Study on the spatial-temporal differences and evolution of ecological security in the typical area of the Loess Plateau - Jiafeng Wen; Kang Hou; Haihong Li; Yue Zhang; Dan He; Ruochen Mei (Environmental Science and Pollution Research, 2021)

Cyanobacterial bloom expansion caused by typhoon disturbance in Lake Taihu China - Huaimin Chen; Yuyang Zhu; Yong Zhang; Xuqing Chen; Ruochen Wang; Wei Zhu (Environmental Science and Pollution Research, 2020)

Antibacterial effects of a polypeptide-enriched extract of Rana chensinensis via the regulation of energy metabolism - Ruochen Wang; Siyu Zhai; Yongtao Liang; Lirong Teng; Di Wang; Guirong Zhang (Molecular Biology Reports, 2020)

Interannual variability of PDSI from tree-ring widths for the past 278 years in Baotou, China - XinJia Zhang; Yu Liu; Huiming Song; Qiufang Cai; Qiang Li; Boyang Zhao; Han Liu; Ruochen Mei (Trees, 2017)

Tree-ring-width-based PDSI reconstruction for central Inner Mongolia, China over the past 333 years - Yu Liu; Xinjia Zhang; Huiming Song; Qiufang Cai; Qiang Li; Boyang Zhao; Han Liu; Ruochen Mei (Climate Dynamics, 2017)

Effect of silicate supplementation on the alleviation of arsenite toxicity in 93-11 (Oryza sativa L. indica) - Haichao Hu; Junting Zhang; Hong Wang; Ruochen Li; Fengshan Pan; Jian Wu; Ying Feng; Yeqing Ying; Qingpo Liu (Environmental Science and Pollution Research, 2013)